Phenomenology of obsessive-compulsive disorder in children and adolescents: sample from a tertiary care center in İstanbul, Turkey - ERDOĞDU, AYŞE BURCU (My University, 2022)
BACKGROUND Obsessive-compulsive disorder (OCD) is a heterogeneous disease in many respects and exhibits this diversity in terms of phenomenology. It also displays several different characteristics in children compared to adults. AIM To describe the socio-demographic and phenomenological features of children with OCD and to investigate the impact of these features on response to pharmacotherapy. METHODS This retrospective study was carried out with 150 children and adolescents who had been diagnosed with OCD between 2014 and 2018. Data was collected by examining the files of the patients with diagnosis of OCD and similar disorders from the hospital database. Yale-Brown Obsessive-Compulsive Scale for Children was used for the assessment of obsession-compulsion subtypes. The Clinical Global Impression (CGI) scale was used to evaluate the severity of the disease (CGI-S) and global improvement (CGI-I). The predictors of treatment response were evaluated using linear regression analysis. The level of significance for all statistic tests was set as P < 0.05. RESULTS The sample was divided into prepubertal (44%) and adolescent (56%) age groups. The most prevalent obsessions were contamination and aggression obsessions, and the most frequent compulsions were washing and checking. While contamination was observed more commonly in the prepubertal age group, the religious obsession was seen more frequently in adolescents. Patients with aggression obsession presented a higher frequency of comorbid anxiety (P = 0.022) and mood P = 0.047) disorder. CGI-I scores did not differ according to phenomenological subgroups (P > 0.05). A lower CGI-I score was linked to a lower CGI-S score (95% confidence interval 0.21-0.39, P < 0.001) and the prepubertal age of admission (95% confidence interval 0.03-0.87, P = 0.020). CONCLUSION The phenomenology of OCD shows differences depending on the age group and the comorbid psychiatric disorders. Earlier identification and treatment of OCD may help to prevent the impairment of the mental health of children and adolescents.
Keywords: Obsessive-compulsive disorder; Phenomenology; Comorbidity; Treatment response; Serotonin reuptake inhibitors